2017
DOI: 10.1136/vr.104107
|View full text |Cite
|
Sign up to set email alerts
|

Private animal health and welfare standards in quality assurance programmes: a review and proposed framework for critical evaluation

Abstract: In recent years, 'private standards' in animal health and welfare have become increasingly common, and are often incorporated into quality assurance (QA) programmes. Here, we present an overview of the use of private animal health and welfare standards in QA programmes, and propose a generic framework to facilitate critical programme review. Private standards are being developed in direct response to consumer demand for QA, and offer an opportunity for product differentiation and a means to drive consumer choi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 23 publications
(34 reference statements)
1
27
0
Order By: Relevance
“…According to Main and co-workers [ 14 ], a private standard’s aim should be to improve animal welfare and not only certify compliance with the governmental minimum legislation. According to More and co-workers [ 3 ], two of the first questions for a policy maker to ask and determine is what the private standard’s goal and intention should be when it comes to animal welfare, and who should benefit from the standard. These questions would perhaps be obvious to most of us.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…According to Main and co-workers [ 14 ], a private standard’s aim should be to improve animal welfare and not only certify compliance with the governmental minimum legislation. According to More and co-workers [ 3 ], two of the first questions for a policy maker to ask and determine is what the private standard’s goal and intention should be when it comes to animal welfare, and who should benefit from the standard. These questions would perhaps be obvious to most of us.…”
Section: Discussionmentioning
confidence: 99%
“…The paper is based on discussions emanating from our project Mind the Gaps! From Intentions to Practice in Animal Welfare Legislation and Private Standards [ 13 ], but also on results from other research groups and studies, such as those by More and co-workers [ 3 ], who identified a need for greater scrutiny of private standards, and Main and co-workers [ 14 ], who have presented a framework for developing private standards with an aim to improve animal welfare. They have, however, not scrutinesed the relation between existing regulations and the effect of the control outcomes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, each European member states has developed national action plans, including limiting antimicrobial usage in farm animals. A large number of management strategies are relevant, but may vary between farms and regions, including Quality Assurance Schemes [ 51 ], biosecurity, vaccination and on-farm diagnostic testing. It is clear that an integrated approach is needed, including improved on-farm management of herd health, ongoing measurement and benchmarking of on-farm antimicrobial usage, and relevant education and training.…”
Section: Discussionmentioning
confidence: 99%